Levocarnitine Supplementation Affects Adiponectin and Serum Lipid Levels in Type 2 Diabetic Mice - Shahida Parveen, Irfan Afzal Mughal, Noor-Ul-Ain Irfan, Ilqa Attique Ahmed, Amna Faruqi, Asma Irfan (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To ascertain the impact of levocarnitine on adiponectin and serum lipid levels in a T2DM mouse model. Design of the study: Randomized controlled trial Place and Duration of Study: Department of Physiology, Army Medical College, Rawalpindi from 1stSeptember 2015 to 31stAugust 2017. Methodology: Forty healthy BALB/c mice, which were allocated to two groups. The mice were initially given a high-fat diet for a fortnight and then induction of T2DM was performed by injecting them with streptozotocin intraperitoneally. Group I was taken as diabetic control, and group II was given levocarnitine. After six additional days, blood samples were analyzed for insulin, adiponectin and lipids. Results: Adiponectin blood level was significantly increased and an improvement in lipid profile was observed in the levocarnitine group, when compared with control group. In the diabetic control group, a positive significant correlation was observed between (HDL-C) high density lipoprotein levels and adiponectin levels. Additionally, this group also showed total cholesterol and low-density lipoproteins (LDL-C) are negatively proportionate to the adiponectin. Conclusions: The addition of levocarnitine increases serum adiponectin levels and improves dyslipidaemia in a type of diabetic rats.